KEKUATAN MENGIKAT HUKUM DALAM PERSPEKTIF MAZHAB HUKUM ALAM DAN MAZHAB POSITIVISME HUKUM - Hadi, Syofyan (Faculty of Law, University of Muhammadiyah Malang, 2017)
The existence of society is always followed by the existence of law. It indicates that society and law can not be separated from one another. The law is not only an instrument to create security and order relationships between individuals and other individuals in society. However, the law is also an instrument of morality that enters the human ratio to create justice. Related to that, in law there are two most famous schools of law, the school of natural law and legal positivism madhabab. Through the literature study approach, this study tries to answer the strength of binding power between the school of natural law and the school of legal positivism of the School of Natural Law sees the law as a reflection of morals, ethics and justice. While the legal positivism madhhab see law as a sovereign command that has nothing to do with morals, ethics and justice